2012
DOI: 10.1007/s00125-012-2546-9
|View full text |Cite
|
Sign up to set email alerts
|

Delta cell secretory responses to insulin secretagogues are not mediated indirectly by insulin

Abstract: Aims/hypothesis Somatostatin from islet delta cells inhibits insulin and glucagon secretion, but knowledge of the regulation of pancreatic somatostatin release is limited. Some insulin secretagogues stimulate somatostatin secretion, and here we investigated whether delta cell secretory responses are indirectly regulated in a paracrine manner by insulin released from beta cells. Methods Hormone release from static incubations of primary mouse islets or somatostatin-secreting TGP52 cells was measured by RIA. mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
5
12
0
Order By: Relevance
“…These data are consistent with a substantial body of earlier work [2939]. In addition, we observed that the muscarinic cholinergic agonist CCh inhibited glucose-induced somatostatin secretion, in accord with Hauge-Evans et al [33, 34]. Importantly, it should be noted that muscarinic cholinergic receptor isoforms are expressed differentially in beta and delta cells and, as a consequence, their responses to parasympathetic stimulation are different.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are consistent with a substantial body of earlier work [2939]. In addition, we observed that the muscarinic cholinergic agonist CCh inhibited glucose-induced somatostatin secretion, in accord with Hauge-Evans et al [33, 34]. Importantly, it should be noted that muscarinic cholinergic receptor isoforms are expressed differentially in beta and delta cells and, as a consequence, their responses to parasympathetic stimulation are different.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, it should be noted that muscarinic cholinergic receptor isoforms are expressed differentially in beta and delta cells and, as a consequence, their responses to parasympathetic stimulation are different. Beta cells express the M3 isoform (whose agonists stimulate insulin secretion), whereas the M2 and M4 isoforms are involved in the parasympathetic inhibition of somatostatin secretion from delta cells [33]. In our studies, each of the three GPR120 agonists tested caused a marked inhibition of glucose-induced somatostatin secretion.…”
Section: Discussionmentioning
confidence: 74%
“…The crosstalk between these cells forms a finely tuned network that controls hormone release and maintains normal growth and survival of the islets. For example, somatostatin secreted from the islet delta cells regulates the responses of the islet beta and alpha cells to physiological changes [1,2]. An increase in the circulating glucose concentration triggers the release of somatostatin from the pancreatic delta cells, which exerts inhibitory effects on both insulin secretion from the beta cells and glucagon secretion from the alpha cells [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin, in turn, is thought to stimulate ␦-cells to release SST, which suppresses both insulin/glucagon release. However, recent data indicate that factors other than insulin may be involved in the glucose-induced rise in SST (28). Nevertheless, the critical role that SST plays in the paracrine regulation of islet function is supported by studies showing enhanced glucosestimulated insulin secretion (GSIS) in islets from SST-KO mice (13).…”
Section: Role Of Endogenous Sst In Basal and L-argstimulated Insulin mentioning
confidence: 96%